The microbiota’s funnel effect: How multiple factors independently converge in changing the microbiota - Agnoletti, Massimo; Fasano, Alessio (PNEI Review - Open access, 2025)
The science of the microbiota, by revealing the complexity of interactions between the world of microorganisms that colonize us and that of human cells, represents the dawn of a new paradigm in biomedical and psychological sciences. It allows for a more complex yet more promising perspective on human health and disease compared to previous approaches. Scientific literature has now identified specific lifestyle‐related factors (nutrition, environmental physicalchemical quality, psychological well‐being, etc.) that significantly influence the composition of the microbiota. This paper introduces the concept of the “funnel effect” of the microbiota to describe the convergent and partially independent nature of these factors (nutrition, physical activity, psychological well‐being, sleep quality, social support, environmental physical‐chemical quality, circadian rhythms) on the composition of the intestinal microbiota, thereby impacting the overall health of the human organism. The “funnel effect” of the microbiota has some highly relevant clinical implications, emphasizing the need for an integrated psycho‐neuro‐endocrineimmunological approach, in contrast to the highly specialized and molecularly focused approach that is currently widely adopted.